Design and development of an in-house multiplex RT-PCR assay for simultaneous detection of HIV-1 and HCV in plasma samples - M Paryan; M Forouzandeh-Moghadam; V Kia; S Mohammadi-Yeganeh; Raz A Abbasali; Samiee S Mirab (Iranian Journal of Microbiology, 2012)
Background and Objectives: HIV-1 and HCV infections are life threatening problems in patients who receive blood products. Serological methods have proven useful in detecting these infections, but there are setbacks that make it challenging to detect these infectious agents. By the advent of Nucleic Acid Testing (NAT) methods, especially in multiplex format, more precise detection is possible. Materials and Methods: We have developed a multiplex RT-PCR assay for simultaneous detection of HIV-1 and HCV. Primers were designed for highly conserved region of genome of each virus. Using these primers and standard plasmids, we determined the limit of detection, clinical and analytical specificity and sensitivity of the assay. Monoplex and multiplex RT-PCR were performed. Results: Analytical sensitivity was considered to be 100 and 200 copies/ml for HIV-1 and HCV, respectively. High concentration of one virus had no significant effect on the detection of the other one with low concentration. By analysis of 40 samples, clinical sensitivity of the assay was determined to be 97.5%. Using different viral and human genome samples, the specificity of the assay was evaluated to be 100%. Conclusions: The aim of this study was to develop a reliable, rapid and cost effective method to detect HIV-1 and HCV simultaneously. Results showed that this simple and rapid method is perfectly capable of detecting two viruses in clinical samples.